Pengaruh Sistem Pengendalian Internal Pemerintah Terhadap Kinerja Pemerintah Daerah - Mattoasi Mattoasi; Didiet Pratama Musue; Yaman Rauf (Jambura Accounting Review, 2021)
PThis study aims to determine the effect of the internal control system on the performance of local government Case Study in Gorontalo Regency. This study uses quantitative research methods, and the data sources use primary data obtained from questionnaires distributed to respondents. Meanwhile, the data analysis used in this research is descriptive quantitative analysis using statistical t-test and coefficient of determination test (ajusted R-Square). The results showed that the internal control system had a positive effect on the performance of local governments with a determinant value of 48.7%. The result of this study contribute to the government to establish and implement a more effectives Internal Constrol Systems (ICS).